Association between prenatal provision of lipid‐based nutrient supplements and caesarean delivery: Findings from a randomised controlled trial in Malawi. Issue 4 (31st July 2022) - Salenius, Meeri; Pyykkö, Juha; Ashorn, Ulla; Dewey, Kathryn G.; Gondwe, Austrida; Harjunmaa, Ulla; Maleta, Kenneth; Nkhoma, Minyanga; Vosti, Stephen A.; Ashorn, Per; Adubra, Laura
Abstract: In populations with a high prevalence of childhood and adolescent undernutrition, supplementation during pregnancy aiming at improving maternal nutritional status and preventing fetal growth restriction might theoretically lead to cephalopelvic disproportion and delivery complications. We investigated whether the prenatal provision of small‐quantity lipid‐based nutrient supplements (SQ‐LNS) was associated with an increased risk of caesarean section (CS) or other delivery complications. Pregnant Malawian women were randomised to receive daily i) iron–folic acid (IFA) capsule (control), ii) multiple micronutrient (MMN) capsule of 18 micronutrients (second control), or iii) SQ‐LNS with similar micronutrients as MMN, plus four minerals and macronutrients contributing 118 kcal. We analysed the associations of SQ‐LNS, CS, and other delivery complications using log‐binomial regressions. Among 1391 women enrolled, 1255 had delivery information available. The incidence of CS and delivery complications was 6.3% and 8.2%, respectively. The incidence of CS was 4.0%, 6.0%, and 8.9% ( p  = 0.017) in the IFA, MMN, and LNS groups, respectively. Compared to the IFA group, the relative risk (95% confidence interval) of CS was 2.2 (1.3–3.8) ( p  = 0.006) in the LNS group and 1.5 (0.8–2.7) ( p  = 0.200) in the MMN group. We found no significant differences for other delivery complications. Provision of SQ‐LNS to pregnant women may have increased the incidence of CS. The baseline rate was, however, lower than recommended. It is unclear if the higher CS incidence in the SQ‐LNS group resulted from increased obstetric needs or more active health seeking and a better supply of services. Trial registered at clinicaltrials.gov, NCT01239693. Abstract : Provision of lipid‐based nutrient supplements (LNS) to pregnant Malawian women was associated with a higher incidence of caesarean delivery compared with iron–folic acid (IFA), which is the standard of care. The overall rate of caesarean section in this study was lower than recommended, and it remains unclear if the increased incidence in the LNS group resulted from increased obstetric needs or more active health seeking and a better supply of services. The association of LNSs with higher caesarean delivery risk is a possible phenomenon in some settings and calls for monitoring obstetric complications in future prenatal nutritional supplementation studies and programs. Key messages: Provision of lipid‐based nutrient supplements (LNS) to pregnant Malawian women was associated with a higher incidence of caesarean delivery compared with iron–folic acid, which is the standard of care. The overall rate of caesarean section in this study was lower than recommended, and it remains unclear if the increased incidence in the LNS group resulted from increased obstetric needs or more active health seeking and a better supply of services. The association of LNS with higher caesarean delivery risk is a possible phenomenon in some settings and calls for monitoring obstetric complications in future prenatal nutritional supplementation studies and programs.